2014
DOI: 10.1261/rna.044701.114
|View full text |Cite
|
Sign up to set email alerts
|

The MID-PIWI module of Piwi proteins specifies nucleotide- and strand-biases of piRNAs

Abstract: Piwi-interacting RNAs (piRNAs) guide Piwi Argonautes to suppress transposon activity in animal gonads. Known piRNA populations are extremely complex, with millions of individual sequences present in a single organism. Despite this complexity, specific Piwi proteins incorporate piRNAs with distinct nucleotide-and transposon strand-biases (antisense or sense) of unknown origin. Here, we examined the contribution of structural domains in Piwi proteins toward defining these biases. We report the first crystal stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 44 publications
3
75
0
Order By: Relevance
“…In the case of Ago silencing via non-slicer mechanisms, GW182-family proteins, named for their enrichment in glycine and tryptophan residues, are recruited to RISC (reviewed in [105]) through interactions with the PIWI domain [91,95] (Fig. 2a).…”
Section: Hhmi Author Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of Ago silencing via non-slicer mechanisms, GW182-family proteins, named for their enrichment in glycine and tryptophan residues, are recruited to RISC (reviewed in [105]) through interactions with the PIWI domain [91,95] (Fig. 2a).…”
Section: Hhmi Author Manuscriptmentioning
confidence: 99%
“…Our current understanding of the molecular mechanisms of Piwi proteins is primarily based on numerous genetic screens, biochemical assays, and comparisons to their Ago counterparts. The existing structural data on eukaryotic Piwis focuses on individual domains, specifically the 3′-binding PAZ domain and 5′-binding MID domain [105,106], both of which show extensive interactions with the ends of the RNA guide. As is the case for Ago, the 5′ phosphate is bound tightly by the MID-PIWI lobe and the identity of the 5′ nucleotide is "read" by the nucleotide specificity loop [105].…”
Section: Hhmi Author Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…We first checked for typical piRNA features like the 1U bias that results from 5 ′ Uridine recognition of Piwi proteins (Cora et al 2014). We found that the 26-34 nt fraction, but not the 18-25 nt fraction exhibits a strong bias for Uridine at position 1 (Fig.…”
Section: Identification Of Pirnasmentioning
confidence: 99%